Itikad Baik Pembeli Tanah Sebagai Jaminan Perlindungan Hukum Terhadap Wanprestasi Penjual (Studi Kasus Putusan No. 9/Pdt.G/2018/PN.Kln.) - Anggriani, Reni; Fadilla, Firdha Ikhsania (Universitas Brawijaya, 2023)
This research aims to analyse how the protection of the Buyer of the land in the event of a default is carried out by the Seller. This research method is empirical normative, namely from laws and regulations and interviews of speakers related to this paper. Based on Article 1338 paragraph (3) of the Civil Law and Supreme Court Circular No. 4 of 2016 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2016, which is a guideline for the implementation of duties for the judiciary, the Formulation of the General Civil Chamber Number 4, is stated that Good faith when purchasing land is one of the legal protections for the Purchaser of the land, so it is necessary to obtain a guarantee of legal protection.